Analysis of Transportation Mode Choice for Commuting To Campus (Case Study: Undergraduate and Graduate Students of the Faculty of Engineering Muhammadiyah University of Yogyakarta) - Debby Anggriawan Poetra; Bagus Hario Setiadj; Ismiyati (Jurnal Teknik Sipil dan Perencanaan, 2025)
The parking lot density at the Faculty of Engineering, Universitas Muhammadiyah Yogyakarta (UMY), reflects students' high use of motor vehicles. Various factors, including demographic characteristics, travel patterns, and the availability and limitations of public transportation infrastructure, influence this. However, no specific research has analyzed students' transportation mode choices at the Faculty of Engineering UMY and their impact on the campus parking capacity. This study aims to describe students' demographic and travel characteristics and analyze the parking capacity at the Faculty of Engineering UMY. The methods used were descriptive statistics and cross-tabulation analysis by distributing questionnaires to 98 respondents. The results show that most respondents are male, within the age range of 19-23 years. Most students have an income higher than the Provincial Minimum Wage (UMP), enabling them to own a private vehicle or pay for transportation costs. The primary transportation mode used by students is motorcycles. Private motorcycles dominate the transportation choice due to their efficiency for short trips (0-15 minutes or 1-7 km). Parking capacity analysis shows that the parking capacity for two-wheeled vehicles at the Faculty of Engineering UMY has exceeded its capacity with a saturation rate 1.21 during peak hours. Meanwhile, the parking facility or four-wheeled vehicles has reached 100%, with a saturation rate of 1, indicating that it is complete but has not exceeded capacity during peak hours. The conclusion of this study emphasizes that the choice of transportation mode for students at the Faculty of Engineering UMY is dominated by private vehicles, particularly motorcycles. This condition results in high parking saturation, which calls for transportation management strategies such as improving public transportation accessibility, regulating private vehicle usage policies, and optimizing parking spaces.